Cell-to-Cell Spread of Retroviruses. - Sattentau, Q (2010)
Viruses from several families use direct cell-to-cell infection to disseminate between cells. Retroviruses are a relatively recent addition to this list, and appear to spread cell-to-cell by induction of multimolecular complexes termed virological synapses that assemble at the interface between infected and receptor-expressing target cells. Over the past five years, detailed insight into the cellular and molecular basis of virological synapse-mediated retroviral cell-to-cell spread has been obtained, but important questions and controversies have been raised that remain to be resolved. This review will focus on recent advances in the field with emphasis on areas in which work still needs to be done.